The (lack of) transparency of the funding received by parliamentary groups: a study in the light of Spanish Law - GONZÁLEZ-JULIANA, Álvaro (Revista Jurídica Portucalense, 2024)
The scarce regulation of subsidies granted to parliamentary groups, together with the absence of their control by the Chambers, makes it urgent to ensure transparency in the use of these public funds in order to ensure to guarantee true accountability. This article analyses the applicability of the Spanish Law 19/2013, of 9 December, on transparency, access to public information and good governance to these subsidies, highlighting the insufficiency of active publicity in this area and the difficulties in in making the right of access to this information effective.